Education for what? Human capital, human rights, and protection discourses in the COVID-19 response - Boisvert, Kayla (Frontiers in Education, 2022)
The rallying cry of global actors working on education during COVID-19 has been that the pandemic poses a grave threat to ensuring equitable and inclusive access to high quality education for all children and adolescents, grounding the response firmly in the domain of global commitments embodied in Sustainable Development Goal 4, as well as prior commitments to education for all. However, while the idea of a global goal signifies cohesion around a shared set of ideals and actions, the meaning of these global commitments is contested terrain. It is just this terrain—alongside other cultural, political, and economic forces—that has the potential to affect national education responses to COVID-19, as well as the meaning of education writ large. This article explores three discourses—Education for Human Capital, Education as a Human Right, and Education for Protection—during COVID-19, demonstrating the way the idea of a collective response to the pandemic masks deep ideological difference between global actors. The article traces the evolution of these discourses in education in development and education in emergencies, situating them within broader cultural, political, and economic phenomena. This history is used to ground an analysis of the discourses within the COVID-19 education response and raises questions about the impacts these discourses may have on national education systems and education writ large during and beyond the pandemic.